Description of the final instar larva of Acrogomphus jubilaris Lieftinck, 1964 (Odonata, Gomphidae), with information on the distribution of Acrogomphus in Borneo - Butler, Stephen G.; Steinhoff, Philip O. M.; Dow, Rory A. (Zootaxa, 2016)
The final instar larva of Acrogomphus jubilaris Lieftinck, 1964, is described and figured for the first time based on exuviae from four male and one female larvae collected in Sarawak, Malaysian Borneo. The adults of A. jubilaris are very rarely encountered. The larvae, however, are surprisingly common in forest streams in Borneo. It is compared with A. malayanus Laidlaw, 1925 and A. walshae Lieftinck, 1935, and notes on behavior, distribution and habitat are included. A map including all known records of A. jubilaris is provided.